PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VII G SMP NEGERI 3 SUKOHARJO - Sri Murwani (Universitas Veteran Bangun Nusantara, 2020)
The objective of this classroom action research is to improve students' learning achievement of Mathematics through Discovery Learning Model in the class of VII during the 2nd semester at SMP Negeri 3 Sukoharjo in the academic year 2019/ 2020. This research is conducted from January to Juni 2020 at SMP Negeri 3 Sukoharjo. The subjects are 32 students of class VII G. This research is desaigned in two cycles. The data collection techniques are documentation, observation, and written tests. The data collection tools are observation sheets, test items, and score list documents. Analysis data use comparative descriptive analysis followed by reflection on each cycle consists of four steps, namely: (1) Planning, (2) Action Implementation, (3) observation, and (4) reflection. The results of this research indicate the increasing in students’ mathematics learning achievement. It can be seen from the average of learning achievement score of mathematics subjects, where the average score before action is 64,5, the average score of the first cycle is 72,3 and average score of the second cycle is 80,2. In addition, the percentage of students' learning mastery increase, before the action of 40,6%, in the first cycle of 68,8% and in the second cycle of 90,6%. So, it can be concluded that the Discovery Learning can improve the learning process and the mathematics learning achievement in the class VII G during the 2nd semester at SMP Negeri 3 Sukoharjo in the academic year 2019/ 2020.